Transcriptomics Profile Of Long Noncoding Rnas And Protein-coding Genes In Aedes Aegypti Cells Infected With Dengue Virus 1 - Obeidat, Sattam Mohammad Ali (2021)
Dengue virus (DENV) of the Flaviviridae family is a mosquito-borne virus which cause dengue disease in several tropical and sub-tropical areas. It is transmitted by Aedes mosquitoes, and Ae. aegypti is the main vector. Many studies focused on the functions of protein-coding genes in virus-host interaction. Non-coding genes such as long non-coding RNAs (lncRNAs) have shown to have potential role in virus-host interaction. Previous studies showed that lncRNAs have important roles such as development, virus-host interaction and immunity. However, information on the functions of Ae. aegypti lncRNAs are still incomplete. Thus, in this research, in order to complete the set of lncRNAs in the reference genome a genome-wide identification and characterization of Ae. aegypti lncRNAs were performed using high depth RNAsequencing data sets and vigorous bioinformatics tools. Total number of 4689 novel long non-coding RNAs were systematically identified and characterized, and they were added to the reference genome. Among these novel long non-coding RNAs, 2,064 were intergenic, 2076 and 549 were intronic and antisense respectively. Moreover, it was found that the characteristics of Ae. aegypti novel lncRNAs were similar to lncRNAs discovered in other species like lower GC content, shorter in length, more repeat sequences, and lower sequence conservation compared to protein-coding genes. Furthermore, list of accurate and vigorous differentially expressed genes was one of the targets in this project. As a result, transcriptome profile of Ae